Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Underpricing Saham - Lusiawati, Lusiawati; Novius, Andri; Elisanovi, Elisanovi; Martias, Dony (IRPI Publisher, 2022)
The purpose of this study is to determine the factors that influence the level of stock underpricing. Stock underpricing is a phenomenon that often occurs when a company conducts an Initial Public Offering (IPO) of its company's shares on the Stock Exchange. Underpricing phenomenon is the practice of listing an initial public offering (IPO) at a price below its real value in the stock market. Underpricing conditions can be detrimental to companies as issuers because the funds obtained from the public are not optimal. The variables used in this study are company Firm Age (X1), Firm Size (X2), ROA (X3) and Underpricing (Y). This study uses secondary data obtained through the Indonesian Stock Exchange. The number of samples used was 40 companies with a purposive sampling method. The technique used in data analysis is the calculation of the dependent variable and independent variables, normality test, classical assumption tests and multiple linear regression analysis for hypothesis tests. Based on the results of data analysis, Firm Age and Firm Size have no effect on underpricing. Meanwhile, ROA has a positive effect on underpricing. Keywords: Underpricing, IPO, Shares, Firm Age, Firm Size, ROA.